The Function of FGFR1 Signalling in the Spinal Cord: Therapeutic Approaches Using FGFR1 Ligands after Spinal Cord Injury. (18th January 2017) - Haenzi, Barbara; Moon, Lawrence D. F.
Abstract : Extensive research is ongoing that concentrates on finding therapies to enhance CNS regeneration after spinal cord injury (SCI) and to cure paralysis. This review sheds light on the role of the FGFR pathway in the injured spinal cord and discusses various therapies that use FGFR activating ligands to promote regeneration after SCI. We discuss studies that use peripheral nerve grafts or Schwann cell grafts in combination with FGF1 or FGF2 supplementation. Most of these studies show evidence that these therapies successfully enhance axon regeneration into the graft. Further they provide evidence for partial recovery of sensory function shown by electrophysiology and motor activity evidenced by behavioural data. We also present one study that indicates that combination with additional, synergistic factors might further drive the system towards functional regeneration. In essence, this review summarises the potential of nerve and cell grafts combined with FGF1/2 supplementation to improve outcome even after severe spinal cord injury.